2022
DOI: 10.1136/bmjopen-2022-066650
|View full text |Cite
|
Sign up to set email alerts
|

Improving experience of medical abortion at home in a changing therapeutic, technological and regulatory landscape: a realist review

Abstract: ObjectiveTo inform UK service development to support medical abortion at home, appropriate for person and context.DesignRealist reviewSetting/participantsPeer-reviewed literature from 1 January 2000 to 9 December 2021, describing interventions or models of home abortion care. Participants included people seeking or having had an abortion.InterventionsInterventions and new models of abortion care relevant to the UK.Outcome measuresCausal explanations, in the form of context-mechanism-outcome configurations, to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Our data are unable to explain why there is an association between opt-in codeine and greater satisfaction with pain management; however, we postulate that the opt-in approach prompted clinicians to have a more detailed discussion of pain, which better prepared patients for the experience. Our findings align with results from qualitative abortion research that suggest that patients value information, preparation and choice as markers of quality abortion care 24–26. Evidence also shows that pre-abortion information, particularly regarding pain and side effects, can reduce anxiety during the abortion and create a more positive experience overall 27…”
Section: Discussionsupporting
confidence: 83%
“…Our data are unable to explain why there is an association between opt-in codeine and greater satisfaction with pain management; however, we postulate that the opt-in approach prompted clinicians to have a more detailed discussion of pain, which better prepared patients for the experience. Our findings align with results from qualitative abortion research that suggest that patients value information, preparation and choice as markers of quality abortion care 24–26. Evidence also shows that pre-abortion information, particularly regarding pain and side effects, can reduce anxiety during the abortion and create a more positive experience overall 27…”
Section: Discussionsupporting
confidence: 83%
“…The importance of overall choice, highlighted by our participants at several points in the abortion path, resonates with other empirical evidence. 33 , 48 While many of the women we interviewed would have changed nothing about their abortion experience, a few claimed that, in hindsight, they might have chosen an alternative abortion method. Studies comparing satisfaction levels in medical and surgical abortion 49 51 suggest that, were all women able to fully exercise choice, the proportion of abortions that are medically induced could be lower than the current rate in Britain of almost 9 in 10.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study conducted in England during the COVID‐19 pandemic, we found that women were overwhelmingly in favor of home self‐management of medical abortion, but some stressed that the option of an in‐person interaction with health practitioners should remain available 34 . Personal and informed choice pertaining to the abortion method and its location is crucial, and should remain available and accessible 13,35,36 …”
Section: Discussionmentioning
confidence: 99%
“…34 Personal and informed choice pertaining to the abortion method and its location is crucial, and should remain available and accessible. 13,35,36…”
Section: Discussionmentioning
confidence: 99%